Challenging Southeast Asian development the shadows of success - Rigg, Jonathan 1959- (London Routledge, Taylor & Francis Group, 2016)
"Over the course of the last half century, the growth economies of Southeast Asia, Indonesia, Malaysia, the Philippines, Singapore, Thailand and Vietnam, have transformed themselves into middle income countries. This book looks at how the very success of these economies has bred new challenges, novel problems, and fresh tensions, including the fact that particular individuals, sectors and regions have been marginalised by these processes"--Provided by publisher.
The shadows of success: a cautionary tale of Southeast Asian development -- Generating growth, sustaining growth, delivering inequality -- The produced poor: another world of poverty and development -- The unreported and uncounted: tracking the living and lives of Southeast Asia's transnational migrants -- Building the neo-liberal family: dislocated families, fragmented -- The poverty of sustainable development in Southeast Asia: economic growth, the environment and people's lives -- The politics of poverty and development: branch and root -- More growth, less development?
Keywords: Economic development -- Southeast Asia -- Social aspects; Poverty -- Southeast Asia